To Promote or Not to Promote? The Role of the Judiciary in the New Zealand Commercial Mediation Market - Morris, Grant (Victoria University of Wellington Law Review, 2022)
Judicial promotion of mediation has been identified as an important way to encourage and increase the amount of commercial mediation in New Zealand. This latest contribution to the New Zealand Commercial Mediation Study (NZCMS) explores the views of District and High Court judges in relation to the use of mediation in their courts. Comparisons are made with earlier NZCMS studies, including the controversial issue of mandatory mediation. While the judiciary is well placed to increase the amount of commercial mediation in New Zealand, this paper concludes that it is unlikely that this potential will be realised under the current civil procedure settings. District and High Court judges possess a good understanding of mediation and its benefits but also prioritise party autonomy in choosing whether to undertake mediation or not.